Pharmacologic inducers of the uric acid exporter ABCG2 as potential drugs for treatment of gouty arthritis - Bojana Ristic; Mohd Omar Faruk Sikder; Yangzom D. Bhutia; Vadivel Ganapathy (Elsevier, 2020)
Uric acid is the end product of purine catabolism and its plasma levels are maintained below its maximum solubility in water (6-7 mg/dl). The plasma levels are tightly regulated as the balance between the rate of production and the rate of excretion, the latter occurring in urine (kidney), bile (liver) and feces (intestinal tract). Reabsorption in kidney is also an important component of this process. Both excretion and reabsorption are mediated by specific transporters. Disruption of the balance between production and excretion leads to hyperuricemia, which increases the risk of uric acid crystallization as monosodium urate with subsequent deposition of the crystals in joints causing gouty arthritis. Loss-of-function mutations in the transporters that mediate uric acid excretion are associated with gout. The ATP-Binding Cassette exporter ABCG2 is important in uric acid excretion at all three sites: kidney (urine), liver (bile), and intestine (feces). Mutations in this transporter cause gout and these mutations occur at significant prevalence in general population. However, mutations that are most prevalent result only in partial loss of transport function. Therefore, if the expression of these partially defective transporters could be induced, the increased number of the transporter molecules would compensate for the mutation-associated decrease in transport function and hence increase uric acid excretion. As such, pharmacologic agents with ability to induce the expression of ABCG2 represent potentially a novel class of drugs for treatment of gouty arthritis. Keywords: Uric acid excretion, Intestine, ABCG2, Loss-of-function mutations, Gouty arthritis, Pharmacologic inducers